A (3, 6)-connected layer with an unprecedented adeninate nucleobase-derived heptanuclear disc. Issue 12 (23rd February 2015) - Liu, Zheng-Yu; Zhang, Hong-Yun; Yang, En-Cui; Liu, Zhong-Yi; Zhao, Xiao-Jun
Abstract : A (3, 6)-connected layer with an adeninate nucleobase-derived Cu II 7 disc was reported, in which six spin-parallel Cu II ions in the exterior of the disc are antiferromagnetically coupled with the central one to give an S = 5/2 ground-state. Abstract : A (3, 6)-connected layer with an adeninate nucleobase-derived Cu II 7 disc was reported, in which six spin-parallel Cu II ions in the exterior of the disc are antiferromagnetically coupled with the central one to give an S = 5/2 ground-state.